NEOLOGISMS AND LOANWORDS IN MODERN ENGLISH: INSIGHTS FROM CORPUS LINGUISTICS AND THE IMPACT OF DIGITAL COMMUNICATION (Web of Teachers: Inderscience Research, 2024)
The English language is evolving at an unprecedented pace, shaped by globalization, cultural exchange, and the proliferation of digital communication. This study explores the evolution of neologisms and loanwords in Modern English through the lens of corpus linguistics, employing large datasets to uncover patterns in vocabulary change. Additionally, it examines the influence of digital platforms, such as social media and online forums, on shaping English grammar and vocabulary. Using the Corpus of Contemporary American English (COCA) and a social media language corpus, this research highlights trends in lexical innovation, the adoption of foreign terms, and the emergence of new grammatical structures. Findings reveal that English’s openness to external influences, combined with digital media’s informal and dynamic nature, is redefining linguistic norms. These changes have implications for understanding language evolution, teaching English as a second language, and maintaining linguistic diversity in the digital age.